Change in left atrioventricular coupling index to predict incident atrial fibrillation: the multi-ethnic study of atherosclerosis (MESA). (4th February 2022) - Pezel, T; Ambale Venkatesh, B; Quinaglia, T; Heckbert, S; Kato, Y; De Vasconcellos, H; Wu, C; Post, W; Henry, P; Bluemke, D; Lima, J
Abstract: Funding Acknowledgements: Type of funding sources: None. BACKGROUND: Left atrial (LA) and left ventricular (LV) structural and functional parameters have independent prognostic values as predictors of atrial fibrillation (AF). PURPOSE: To investigate the prognostic value of a left atrioventricular coupling index (LACI) and average annualized change in LACI measured by cardiac MRI to predict incident AF in a population-based sample from the Multi-Ethnic Study of Atherosclerosis (MESA). METHODS: In a secondary analysis of the prospective Multi-Ethnic Study of Atherosclerosis (MESA) study, 1, 911 study participants, free of clinically recognized AF and cardiovascular disease at baseline, had LACI assessed with cardiac MRI at baseline (Exam 1, 2000-2002), and ten years later (Exam 5, 2010-2012). LACI was defined as the ratio of LA to LV end-diastolic volumes. Univariable and multivariable Cox proportional hazard models were used to evaluate the associations of LACI and average annualized change in LACI (ΔLACI) with incident AF. RESULTS: Among the 1, 911 participants (mean age 59 ± 9 years and 907 men), 87 incident AF events occurred over 3.9 ± 0.9 years following the second imaging (Exam 5). After adjustment for traditional risk factors, greater LACI and ΔLACI were independently associated with AF (HR 1.69, 95% CI[1.46-1.96] and HR 1.71, 95% CI[1.50-1.94], respectively; both p<.001). Adjusted models for LACI and ΔLACI showed improvement in model discrimination compared to currently used AF risk score (CHARGE-AF score) model (AUC: 0.78 vs. 0.74, and AUC: 0.80 vs. 0.74, both p<.001); and to the final model including individual LA or LV parameters for predicting AF incidence (AUC: 0.78 vs. 0.76, and AUC: 0.80 vs. 0.78, both p<.001). CONCLUSIONS: Atrioventricular coupling (LACI) and coupling change (ΔLACI) were strong predictors for AF in a multi-ethnic population. Both had incremental prognostic value for predicting AF over traditional risk factors, and superior discrimination compared to the CHARGE-AF score and to individual LA or LV parameters. ClinicalTrials.gov Identifier: NCT00005487